The End of the Hysterectomy Epidemic and Endometrial Cancer Incidence: What Are the Unintended Consequences of Declining Hysterectomy Rates? - Temkin, Sarah M.; Minasian, Lori; Noone, Anne-Michelle (Frontiers in Oncology, 2016)
Population-level cancer incidence rates are one measure to estimate the cancer burden. The goal is to provide information on trends to measure progress against cancer at the population level and identify emerging patterns signifying increased risk for additional research and intervention. Endometrial cancer is the most common of the gynecologic malignancies but capturing the incidence of disease among women at risk (i.e. women with a uterus) is challenging and not routinely published. Decreasing rates of hysterectomy increase the number of women at risk for disease which should be reflected in the denominator of the incidence rate calculation. Furthermore hysterectomy rates vary within the United States by multiple factors including geographic location, race and ethnicity. Changing rates of hysterectomy are important to consider when looking at endometrial cancer trends. By correcting for hysterectomy when calculating incidence rates of cancers of the uterine corpus, many of the disparities that have been assumed for this disease are diminished.